Implementasi Manajemen Berbasis Sekolah (MBS) pada Sekolah Menengah Atas (SMA) Negeri 3 Kepulauan Aru: Implementation of School Based Management (SBM) at Senior High School (SMA) Negeri 3 Kepulauan Aru - Sedubun, Popy Diana; Ratumanan, Tanwey Gerson; Laurens, Theresia (ITScience (Information Technology and Science), 2024)
This study examines the implementation of School-Based Management (SBM) at SMA Negeri 3 Kepulauan Aru with the aim of evaluating the planning, implementation, and development of educational activities at the school. The method used is a descriptive qualitative approach through interviews with the principal, teachers, and school committee as well as a review of documents related to school planning, curriculum, and learning activities. The results of the study indicate that educational activity planning is carried out through the preparation of the School Development Plan (RPS) and involves various related parties. The curriculum implemented includes the 2013 Curriculum and the Merdeka Curriculum, adjusted to the school's vision and mission. However, several obstacles were still found in the implementation, including limited teaching staff and lack of attention to extracurricular activities. Supervision by the principal is carried out routinely to ensure the quality of learning and improve teacher professionalism. Overall, SMA Negeri 3 Kepulauan Aru has implemented SBM, but there is room for improvement in terms of community involvement and optimization of learning activities.